La gestión gerencial y la competitividad comercial en la Cooperativa de Ahorro y Crédito PAÍS. - Guananga Guaman, Myriam Fernanda (2024)
ABSTRACT: The main objective of this research study was to focus on the general management is of great importance in the commercial activity of Credit Unions because it allows for effective strategic planning, informed decision making and efficient supervision of daily activities. In this sense, the general objective of this research is to determine how management has an impact on the commercial competitiveness of the credit PAÍS and credit cooperative. For its development, this research work was based on a descriptive methodology, mixed with a nonexperimental design, which allowed the application of survey and interview techniques, which were applied to the members of the cooperative under study. The population was made up of the total number of collaborators of the cooperative, which were a total of 20 people, due to the fact that it was a finite population, we worked with the total population, that is, it was not necessary to calculate the sample. The results obtained showed a strong and positive correlation in relation to management and the competitiveness of the cooperative, so the alternative hypothesis was accepted, which states that management has an impact on the commercial competitiveness of the credit PAÍS and credit cooperative. Based on the deficiencies detected through the information gathering techniques, the proposal was developed, which consisted of a total of six strategic objectives focused on applying improvements in the cooperative's management. Keywords: Management, management, cooperative, competitiveness, members, services. Reviewed by: Marco Antonio Aquino ENGLISH PROFESSOR C.C. 1753456134